Impact of improved beehives technology adoption on honey production efficiency: empirical evidence from Southern Ethiopia - Kassa Tarekegn; Assefa Ayele (Agriculture & Food Security, 2020)
Abstract Background Kaffa, Sheka and Bench Maji zones of Southern Ethiopia are high honey production areas with dense forest coverage. However, due to the traditional production system, the productivity per hive is low. To exploit this production potential in these zones by increasing productivity per hive, different governmental and non-governmental organizations disseminate improved beehives technologies. Yet, the impact of these disseminated and adopted technologies on honey production has not been determined. Thus, this study aimed to estimate the impact of improved beehive adoption on honey production efficiency. Methodology A multistage sampling technique was used to select 360 sampled households. This study applied a stochastic frontier model to assess the technical efficiency (TE) of honey producers and propensity score matching (PSM) with probit model to analyze adoption decision of improved beehive and its impact on honey production efficiency. Results The finding of this study shows that the number hives, type of beehive used, and proximity to the available forest had a significant and positive effect on honey production. The mean TE was 77% that shows the deviation of actual from optimal production amounts. Beekeeping experience, education, level, cooperative membership, participation in improved beehive technology demonstration and extension contact had significant effects on TE. The result of PSM indicates that the adoption of improved beehive technology has a positive and significant effect on production efficiency, as measured by TE. Farmers who adopted improved beehive technology were less technically inefficient than those who did not adopt. Conclusion Overall, the estimated 19.5% difference in TE among the two groups shows there is considerable room for the improvement of beekeeping by efficient utilization of inputs and also provides strong evidence for the diffusion of improved beehives in Kaffa Sheka and Bench Maji zones.